A study on the perception of secondary students in Manila toward Bahay Nakpil Bautista, Mabini Shrine and Rizal Shrine: a basis for a PR campaign - Chowdhury, Neima G.; Cruz, Ira Y.; Hernandez, Judie Faye L.; Ilaya, Kimberly D. and Jamisola, Racel G. 4 0 16; 5
ABSTRACT This is a study that assessed the awareness, knowledge and attitude of secondary students of Manila toward historical museums such as Bahay Nakpil-Bautista Museum, Mabini Shrine PUP and Rizal Shrine Fort Santiago. The results were used as a basis of a PR campaign that aims to promote historical museums and ignite the nationalism of the students by encouraging them to discover the history of their country more than what is written on the books. Both qualitative and quantitative method were utilized in order to gather data. A survey was conducted among 100 secondary students in Manila from schools such as Juan Nolasco High School, Florentino Torres High School, Jose Abad Santos High School, Ramon Magsaysay High School, Manuel Araullo High School and Victorino Mapa High School. Meanwhile, interviews were conducted with the administration of the three museums, and with National Historical Commission of the Philippines, National Commission for the Culture and Arts, and the National Museum. There are three levels in classifying the perception of the secondary students: first level is their Awareness, second level is Knowledge, and the third level is the Attitude. The study showed that the students have a high awareness when it comes to Rizal Shrine while they have a very low awareness for Mabini Shrine especially on Bahay Nakpil-Bautista Museum. While the same results goes to the level of knowledge of the students toward the three museums. The attitude of the students towards the museums are positive which means they want to visit but reasons like no one will accompany them and they do not know how to go there prevent them to do so. Results also showed that the ideal way to encourage the students to the museums is to engage them with an interactive tour or activity and if someone they know will convince them.
Undergraduate Thesis: (Bachelor of Mass Communication) - Pamantasan ng Lungsod ng Maynila 2016.
Keywords: 2 -- 0; 6; 20; 20; 2